The Effectiveness of Cognitive Behavioral Therapy in Helping Victims of Bullying - Gemisa, Githa; Winata, Alfazri; Fitriani, Wahidah (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2026)
Bullying remains a serious school-based problem because it harms victims’ emotional well-being, academic engagement, and social functioning. Although cognitive behavioral therapy (CBT) has been widely recognized as a promising intervention for bullying victims, recent evidence synthesizing its effectiveness across studies remains limited. Therefore, this study aimed to analyze the effectiveness of CBT in helping victims of bullying through a systematic literature review. This study employed a Systematic Literature Review design. The review instrument consisted of keyword-based search procedures and inclusion–exclusion criteria used to identify relevant studies. Data were collected from Google Search and Google Scholar using the keywords “cognitive behavioral therapy” and “bullying victims,” with the review limited to full-text journal articles published between 2021 and 2025. From 207 identified records, five eligible articles were selected for in-depth review. The data were analyzed through screening, evaluation, and comparison of similarities and differences across the selected studies. The findings show that CBT is effective in reducing anxiety, depression, trauma-related reactions, and low self-esteem among bullying victims, while improving self-confidence, emotional control, social skills, and positive thinking. CBT was found to be applicable in individual and group formats, including techniques such as thought stopping. These findings imply that CBT is not only useful as a therapeutic intervention but also has potential as a preventive school-based approach for building safer and more supportive learning environments.